Ruvbl1 silencing affects reproduction of the corn planthopper, Peregrinus maidis. - César A D Xavier; Clara Tyson; Anna E Whitfield (PLoS ONE)
Ruvbl1 (also known as TIP49, Pontin) encodes an ATPase of the AAA+ protein superfamily involved in several cellular functions, including chromatin remodeling, control of transcription, and cellular development (motility, growth, and proliferation). While its role has been well established in model organisms including vertebrates and invertebrates (e.g. mice, Xenopus and Drosophila), putative functions of Ruvbl1 in non-model insect pests have not been addressed. To exploit Ruvbl1 as a potential target gene for applications in insect control, we used an in-vivo RNA interference (RNAi) approach to evaluate the effect of Ruvbl1 silencing on the physiology of the corn planthopper, Peregrinus maidis. Silencing of P. maidis Ruvbl1 (PmRuvbl1) was correlated with visible morphology changes in female individuals with significant increases in body mass observed at 8 and 12 days after double strand RNA (dsRNA) injection. Ovary function was significantly affected in adult females with PmRuvbl1 silenced, with no mature oocytes observed at 8 and 12 days after gene silencing. Whereas no significant difference in egg laying was observed 4 days after dsRNA injection, significantly fewer eggs were laid in plants at 8 and 12 days after dsRNA treatment. Furthermore, dramatic reductions in egg hatching were observed at all time points after PmRuvbl1 silencing, compared to dsGFP-injected controls. These results extend Ruvbl1 functions as a putative regulator of P. maidis reproduction and demonstrate the potential of Ruvbl1 to be further exploited as a target for developing new technologies (e.g. RNA interference, CRISPR-mediated control) for insect control.